Implementation of a Contextual Teaching Approach in Primary School Education - Kovačevič, Sonja; Barbir, Joško (Revija za elementarno izobraževanje, 2024)
Theoretical discussions and results of empirical research on the contextual approach to teaching and learning point to its effectiveness in realising numerous learning outcomes. The theoretical part of the paper presents the theoretical foundations of the contextual teaching and learning approach, with a focus on constructivist learning theory. The empirical part of the paper presents the results of a study on the implementation of the contextual teaching and learning approach in primary school education from the teachers` perspective. The results indicate that teachers apply the principles of the contextual teaching and learning approach relatively rarely in the teaching process.
Keywords: Contextual teaching and learning approach, constructivist teaching approach, problem-based and project-based teaching, active forms of work in the classroom, learning outcomes.